Measuring and analyzing the emotional engagement exhibited by chinese university students in ideological and political theory courses via the IPTCSSE - Liangliang Wang (PLoS ONE, 2026)
This study investigates the emotional responses and engagement levels of Chinese university students enrolled in Ideological and Political Theory Courses (IPTCs), with particular attention to how curriculum design influences students’ attitudes and feelings. Using the IPTCSSE scale, a quantitative analysis was conducted to measure multiple dimensions of emotional engagement. A total of 3,992 valid questionnaires were collected. Based on the emotional engagement subscale, exploratory and confirmatory factor analyses identified seven underlying factors: interest and belonging, classmates and peers, family and curriculum, emotions and feelings, sense of identification, teacher support and influence, and sense of achievement in courses. Descriptive statistics indicated that students generally evaluated all seven factors positively, and all factors were significantly and positively correlated. Among them, sense of achievement in courses received the highest score, while classmates and peers scored the lowest. Correlation and linear regression analyses further showed that each factor positively predicted emotional engagement in IPTCs. Interest and belonging emerged as the strongest predictor, whereas sense of achievement exerted the smallest predictive effect. Drawing on these findings, the study discusses how emotional engagement can be strategically emphasized to improve the pedagogical effectiveness of IPTCs. The results highlight the importance of fostering interest, belonging, supportive teacher-student relationships, and positive emotional experiences to enhance students’ overall engagement with ideological and political education in China’ s higher education context.